(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The aim of the present study was to develop microemulsion gel of Satranidazole for the treatment of periodontitis. The objective was to increase the solubility of Satranidazole, a lipophilic drug and to enhance depth of penetration of the drug into the periodontal pocket for efficacious treatment of periodontitis. Pseudo ternary phase diagrams were constructed to determine the region of existence of microemulsions prepared using cosurfactant titration method. The formulations were developed using isopropyl myristate, tween 80, ethanol; oleic acid, tween 80, propylene glycol; oleic acid, cremophor RH 40, ethanol. Optimization of formulations was done based on in vitro diffusion studies. The microemulsion was gelled using carbopol 940 as the gelling agent. The formulations were evaluated for pH, viscosity, percent transmittance, centrifugation (phase separation), and characterized by scanning electron microscopy, particle size, zeta potential and polydispersity index. The formulation inhibited the growth of micro organism, Salmonella typhimurium which indicates that the formulation could be used to treat periodontal infection.